2022
DOI: 10.3390/ma15072508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Ultrasonic-Assisted End Milling Forces in 2195 Aluminum-Lithium Alloy

Abstract: To achieve high-quality machining of the 2195 aluminum-lithium alloy, this paper presents an experimental study on the effect of milling processing parameters on milling forces and surface topography, during which conventional milling and longitudinal-torsional ultrasonic vibration milling of the 2195 Al-Li alloy were performed. The characterization of the tool tip trajectory illustrates some of the advantages of ultrasonic machining, which include variable depth of cut and tool chip pulling. The differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Based on the ultrasonic vibration amplitude and experimental cutting parameters in published Refs. [ 6 , 7 , 8 , 9 , 10 , 11 ], the cutting parameters for the experiment are planned and presented in Table 3 . Each cutting experiment has repeated ten times and the experimental cutting force are determined by averaging those cutting force value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ultrasonic vibration amplitude and experimental cutting parameters in published Refs. [ 6 , 7 , 8 , 9 , 10 , 11 ], the cutting parameters for the experiment are planned and presented in Table 3 . Each cutting experiment has repeated ten times and the experimental cutting force are determined by averaging those cutting force value.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of cutting force was reported to be caused by intermittent cutting [ 7 ]. At the same time, the intermittent cutting has also been deemed to contribute to cutting force reduction in radial high-speed ultrasonic vibration cutting [ 8 ]. Moreover, it was reported that low-frequency vibration-assisted machining could improve the machinability of difficult-to-cut materials in which intermittent cutting may not occur [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another research was conducted by Shen et al [12] on the UVAM of aluminum alloy 2A12 in slot milling operation, and the results showed that UVAM reduced the vertical side wall surface roughness; however, the slot bottom surfaces were adversely afected by UVAM, and this is mainly due to the vibrational direction. Wang et al [13] conducted a study on the cutting force comparison between CM and UVAM in 2195 aluminum alloy, and the study showed that UVAM reduced the cutting force component F y up to 62% when the optimum machining conditions were selected; also, due to the reduction of the cutting forces, the surface topography found enhanced compared to CM.…”
Section: Introductionmentioning
confidence: 99%
“…By applying ultrasonic vibration to the tool to remove materials intermittently, the purpose of improving machining efficiency, reducing cutting force and reducing tool wear was realized, which is the characteristic of ultrasonic vibration cutting [1]. Nowadays, ultrasonic vibration cutting has been successfully applied in many processing fields, such as turning [2], milling [3] and drilling [4]. Due to the characteristics of high processing temperature and large cutting force, it is easy to have low processing efficiency and poor surface quality when machining hard and brittle materials such as titanium alloy, ceramics and fiber reinforced composites by traditional cutting methods [5].…”
Section: Introductionmentioning
confidence: 99%